Duit Turus: A solution to conflicts in Dayak traditional marriages - SADIANI, S. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study explored the position of Duit Turus in the Dayak tribe marriage and the philosophy contained in the symbol of the Duit Turus. Participants included the families of the groom, the bride, and people who have received Duit Turus. Data were collected through observation, interviews, and documentation studies and analyzed from sociology and anthropology studies of Islamic law. The results showed that giving Duit Turus to the guests or witnesses in the Dayak wedding procession must be carried after an agreement between the two families of the bride and groom.RESUMEN Este estudio exploró la posición del Duit Turus en el matrimonio de la tribu Dayak y la filosofía contenida en el símbolo del Duit Turus. Los participantes incluyeron a las familias del novio, la novia y las personas que han recibido Duit Turus. Los datos fueron recolectados mediante observación, entrevistas y estudios de documentación y se analizaron desde el punto de vista de los estudios de sociología y antropología del derecho islámico. Los resultados mostraron que dar Duit Turus a los invitados o testigos en la procesión de bodas Dayak debe llevarse a cabo después de un acuerdo entre las dos familias de los novios.